Culture and identity in South African education, 1880-1990. - Cross, M (My University, 1990)
This dissertation deals with the forging of identities in twentieth century South Africa.It is undertaken within the discipline of history of education, but, givenithe complexity of the topic, the writer has adopted an interdisciplinary approach, drawing where appropriate on the methodologies provided by other disciplines. (Abbreviation abstract)
A dissertation submitted to the Faculty of Education, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy.
Keywords: Education -- South Africa.; Ethnicity -- South Africa.; Church and education -- South Africa.